Comparison of Ultraviolet B Light‐Emitting Diodes with Single or Triple Quantum Wells. Issue 14 (28th May 2021) - Kolbe, Tim; Knauer, Arne; Ruschel, Jan; Rass, Jens; Kyong Cho, Hyun; Hagedorn, Sylvia; Glaab, Johannes; Lobo Ploch, Neysha; Einfeldt, Sven; Weyers, Markus
Abstract : Light‐emitting diodes (LEDs) with an emission wavelength of 310 nm containing either a single or a triple quantum well are compared regarding their efficiency and long‐term stability. In addition, the influence of the thickness of the lower quantum well barrier and the quantum well thickness in single quantum well (SQW) LEDs is investigated. Electroluminescence measurements show a 28% higher initial output power for the SQW LEDs compared with the triple quantum well (TQW) LEDs because of larger spatial overlap of the carriers in the SQW as revealed by electro‐optical simulations of the LED heterostructures. However, TQW LEDs show a higher output power than SQW LEDs after 1 h operation under harsh conditions. For SQW LEDs, it is found that for a thicker lower quantum well barrier (65 nm instead of 25 nm) the initial output power decreases by ≈15%. A thicker SQW (3 nm instead of 1.6 nm) reduces the initial output power by even 45% but increases the lifetime by a factor of 6 which is attributed to reduced Auger recombination from an enhanced spatial separation of electrons and holes in the quantum wells due to the quantum‐confined Stark effect. Abstract : Light‐emitting diodes (LEDs) with an emission wavelength of 310 nm containing either a single or a triple quantum well are compared regarding their efficiency and long‐term stability. In addition, the influence of the thickness of the lower quantum well barrier and the quantum well thickness in single quantum well LEDs is investigated.